PENGARUH TAX AVOIDANCE DAN KEPEMILKAN INSTITUSIONAL TERHADAP COST OF DEBT PADA PERUSAHAAN MAKANAN DAN MINUMAN - Assyifayufi Khoirul Nisa; Sartika Wulandari (Jurnal Aplikasi Akuntansi, 2021)
This study aims to examine the effect of Tax Avoidance and Institutional Ownership on the Cost of Debt in food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Foam for the 2016-2019 Period. The research methodology used is quantitative methods and the data source comes from secondary data obtained from the Indonesia Stock Exchange. The sampling technique used the purposive sampling method with annual data and the research period from 2016 to 2019. The data analysis technique used was multiple linear regression by conducting normality tests, classical assumption tests (multicollinearity test, autocorrelation test, heteroscedasticity test) and hypothesis testing. using the T test to test the partial regression coefficient and the F test to test the significance of the effect together with a significance level of 5%. The results of this study indicate that partially the independent variables Tax Avoidance and Institutional Ownership have a significant negative effect on the Cost of Debt in the food and beverage sub-sector manufacturing companies listed on the IDX 2016-2019. Meanwhile, simultaneously the independent variables consisting of Tax Avoidance and Institutional Ownership have a significant effect on the Cost of Debt in the food and beverage sub-sector manufacturing companies listed on the IDX 2016-2019.